Question
upstudy study bank question image url

Given \( f(x)=5 x^{2}-4 \) and \( g(x)=6-\frac{1}{2} x^{2} \), find the following expressions. \( \begin{array}{llll}\text { (a) }(f \circ g)(4) & \text { (b) }(g \circ f)(2) & \text { (c) }(f \circ f)(1) & \text { (d) }(g \circ g)(0)\end{array} \) \( \begin{array}{ll}\text { (a) }(f \circ g)(4)=\square & \text { (Simplify your answer.) }\end{array} \)

Ask by Thornton Deleon. in the United States
Feb 20,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\( (f \circ g)(4) = 16 \)

Solution

To solve the problem, we need to evaluate the compositions of the functions \( f \) and \( g \) at the specified points. Let's break it down step by step. ### Given Functions - \( f(x) = 5x^2 - 4 \) - \( g(x) = 6 - \frac{1}{2}x^2 \) ### (a) Calculate \( (f \circ g)(4) \) 1. **Evaluate \( g(4) \)**: \[ g(4) = 6 - \frac{1}{2}(4^2) = 6 - \frac{1}{2}(16) = 6 - 8 = -2 \] 2. **Now evaluate \( f(g(4)) = f(-2) \)**: \[ f(-2) = 5(-2)^2 - 4 = 5(4) - 4 = 20 - 4 = 16 \] Thus, \( (f \circ g)(4) = 16 \). ### (b) Calculate \( (g \circ f)(2) \) 1. **Evaluate \( f(2) \)**: \[ f(2) = 5(2^2) - 4 = 5(4) - 4 = 20 - 4 = 16 \] 2. **Now evaluate \( g(f(2)) = g(16) \)**: \[ g(16) = 6 - \frac{1}{2}(16^2) = 6 - \frac{1}{2}(256) = 6 - 128 = -122 \] Thus, \( (g \circ f)(2) = -122 \). ### (c) Calculate \( (f \circ f)(1) \) 1. **Evaluate \( f(1) \)**: \[ f(1) = 5(1^2) - 4 = 5(1) - 4 = 5 - 4 = 1 \] 2. **Now evaluate \( f(f(1)) = f(1) \)**: \[ f(1) = 1 \quad \text{(as calculated above)} \] Thus, \( (f \circ f)(1) = 1 \). ### (d) Calculate \( (g \circ g)(0) \) 1. **Evaluate \( g(0) \)**: \[ g(0) = 6 - \frac{1}{2}(0^2) = 6 - 0 = 6 \] 2. **Now evaluate \( g(g(0)) = g(6) \)**: \[ g(6) = 6 - \frac{1}{2}(6^2) = 6 - \frac{1}{2}(36) = 6 - 18 = -12 \] Thus, \( (g \circ g)(0) = -12 \). ### Summary of Results - \( (f \circ g)(4) = 16 \) - \( (g \circ f)(2) = -122 \) - \( (f \circ f)(1) = 1 \) - \( (g \circ g)(0) = -12 \) The final answers are: - (a) \( (f \circ g)(4) = 16 \) - (b) \( (g \circ f)(2) = -122 \) - (c) \( (f \circ f)(1) = 1 \) - (d) \( (g \circ g)(0) = -12 \)

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

To solve the expressions given, let's break down each function and apply the necessary transformations. First, we need to find \( (f \circ g)(4) \): 1. Calculate \( g(4) \): \[ g(4) = 6 - \frac{1}{2}(4^2) = 6 - \frac{1}{2}(16) = 6 - 8 = -2. \] 2. Now substitute this into \( f(x) \): \[ f(-2) = 5(-2)^2 - 4 = 5(4) - 4 = 20 - 4 = 16. \] So, \( (f \circ g)(4) = 16 \). Next, we find \( (g \circ f)(2) \): 1. Calculate \( f(2) \): \[ f(2) = 5(2^2) - 4 = 5(4) - 4 = 20 - 4 = 16. \] 2. Now substitute this into \( g(x) \): \[ g(16) = 6 - \frac{1}{2}(16^2) = 6 - \frac{1}{2}(256) = 6 - 128 = -122. \] So, \( (g \circ f)(2) = -122 \). Next, we find \( (f \circ f)(1) \): 1. Calculate \( f(1) \): \[ f(1) = 5(1^2) - 4 = 5(1) - 4 = 5 - 4 = 1. \] 2. Now substitute this back into \( f(x) \): \[ f(1) = 1 \text{ (already found)}. \] So, \( (f \circ f)(1) = 1 \). Finally, we find \( (g \circ g)(0) \): 1. Calculate \( g(0) \): \[ g(0) = 6 - \frac{1}{2}(0^2) = 6 - 0 = 6. \] 2. Now substitute this into \( g(x) \): \[ g(6) = 6 - \frac{1}{2}(6^2) = 6 - \frac{1}{2}(36) = 6 - 18 = -12. \] So, \( (g \circ g)(0) = -12 \). To summarize: \[ \begin{array}{ll} \text{(a)} & (f \circ g)(4) = 16,\\ \text{(b)} & (g \circ f)(2) = -122,\\ \text{(c)} & (f \circ f)(1) = 1,\\ \text{(d)} & (g \circ g)(0) = -12. \end{array} \]

Related Questions

Latest Pre Calculus Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy